PENGARUH TRAINING SATISFACTION DAN SUPERVISOR SUPPORT TERHADAP AFFECTIVE COMMITMENT KARYAWAN INDUSTRI MANUFAKTUR DI TANGERANG - Cahyo, Sigit Nur; Astuti, Puji (JURNAL LENTERA BISNIS, 2026)
Affective commitment is an important concern as it can have a positive impact on organizations. Training satisfaction and supervisor support have been proven to enhance affective commitment, where training satisfaction is influenced by training orientation, perceived value of training, and organizational support for training, while supervisor support acts as an independent factor that directly affects affective commitment. This study aims to examine the effects of training satisfaction and supervisor support on affective commitment. The research employs a purposive sampling method involving 311 manufacturing employees in Tangerang, with data analyzed using CB-SEM. The findings reveal that training orientation, perceived value of training, and organizational support for training have a positive effect on training satisfaction, which in turn increases affective commitment. Additionally, supervisor support, as another independent variable, is also found to have a positive effect on affective commitment. To maintain a high level of affective commitment, companies need to build training satisfaction through easy access to training, aligned training objectives, and a supportive learning environment that enables employees to apply new competencies. Furthermore, organizations should also consider other factors such as relevant training methods and the competence of instructors in delivering the material.